2019
DOI: 10.1177/0844562119859138
|View full text |Cite
|
Sign up to set email alerts
|

Spaces of Exclusion: Safety, Stigma, and Surveillance of Mothers Experiencing Homelessness

Abstract: Lack of affordable housing, poverty, and intimate partner violence are among the most common reasons for homelessness among mothers and their children in Canada. Mothers experience social exclusion in compounding and debilitating ways. In the literature on social exclusion and health, rarely is safety recognized as a prominent component of social exclusion. The purpose of this critical narrative study was to better understand the unique narratives of social exclusion for mothers experiencing homelessness in On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…As noted by Walters et al ( 52 ), pervasive social exclusion is likely to play a large role in inequitable access to PrEP. Our findings resonate with recent research that has identified exclusion from safety as a driver of risk in marginalized populations ( 53 ) resulting from overt surveillance and discriminatory practices.…”
Section: Discussionsupporting
confidence: 90%
“…As noted by Walters et al ( 52 ), pervasive social exclusion is likely to play a large role in inequitable access to PrEP. Our findings resonate with recent research that has identified exclusion from safety as a driver of risk in marginalized populations ( 53 ) resulting from overt surveillance and discriminatory practices.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests some recognition that mothering is more than a one‐way process from mother to child for the exclusive sake of the child and signals a shift toward a more complex understanding of mothering as more than a practice . This recognition is important given the challenges women mothering in the context of IPV often face in relation to systemic barriers and the long‐term impacts of abuse on multiple aspects of their lives (Benbow et al, 2019; Gilroy et al, 2020; Greaves et al, 2004; Varcoe & Irwin, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Much of the existing nursing research has focused on women marginalized by structural conditions such as those living in shelters or second‐stage housing or experiencing homelessness (Benbow et al, 2019; Gilroy et al, 2020; Nixon et al, 2017; Peckover, 2003); seeking other formalized services such as Infant/child nutritional Supplemental programs, or child protective services (Ellis et al, 2008); from varied ethnic and cultural backgrounds and living on low incomes/in poverty (Benbow et al, 2019; Gilroy et al, 2020; Nixon et al, 2017); experiencing mental health issues (Benbow et al, 2019; Greaves et al, 2004; Lewin et al, 2010) and using substances (Greaves et al, 2004). The tendency to focus on women marginalized by structural conditions may be driven by an assumption that facing significant chronic stress from intersecting structural barriers may lead to child maltreatment, reflecting an expectation of deficient parenting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this surveillance and monitoring reinforces experiences of felt stigma, which is one's sense of inhabiting a devalued status deriving from possessing socially degraded identities leading one to perceive exclusion, rejection, and shame (Scrambler, 2009). Conversely, being the brunt of stigmatization means that one also navigates surveillance based on these perceived devalued statuses (Benbow et al, 2019;Patel, 2012). As such, stigma becomes another mechanism of surveillance; this is a particularly complex process to manage for formerly incarcerated women, as multiple societal marks of "deviance" communicate permanent devalued statuses (Gunn et al, 2018;Leverentz, 2011) and, consequently, reify and reproduce existing inequities of class, race, gender, and sexuality (Parker & Aggleton, 2003).…”
Section: Stigma and Surveillancementioning
confidence: 99%